2020
DOI: 10.1002/ijgo.13099
|View full text |Cite
|
Sign up to set email alerts
|

The role of acculturation in migrants’ use of gynecologic emergency departments

Abstract: Objective To examine whether acculturation of migrant patients is a predictor of non‐urgent use of gynecologic emergency departments (GEDs). Methods A cross‐sectional study based on standardized questionnaire interviews among migrant (n=477) and non‐migrant (n=246) women attending a GED in Berlin, Germany, between 2017 and 2018. Non‐urgent GED use was defined by health system (e.g., no hospital admission) or patient (e.g., low subjective urgency) criteria. Acculturation was assessed by the Frankfurt Acculturat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Only visiting a gynecology emergency clinic compared to internal medicine did modify the size of the association between migration status and adequacy. More detailed results for patients in the present study who visited the gynecology hospital-based outpatient clinic are reported in (19). The observed rate of admission to hospital (40%) was in line with what has been reported elsewhere (6).…”
Section: Discussionsupporting
confidence: 91%
“…Only visiting a gynecology emergency clinic compared to internal medicine did modify the size of the association between migration status and adequacy. More detailed results for patients in the present study who visited the gynecology hospital-based outpatient clinic are reported in (19). The observed rate of admission to hospital (40%) was in line with what has been reported elsewhere (6).…”
Section: Discussionsupporting
confidence: 91%
“…Obwohl die Schlussfolgerungen zum Teil auf einer sehr kleinen Anzahl von Studien beruhen, stellen sie insbesondere bei Personen mit eigener Migrationserfahrung eine geringere Nutzung von Fachärzten und Präventionsprogrammen fest.22 Bezüglich der Inanspruchnahme von Allgemeinmedizinern, Krankenhausaufenthalten, Notfalldiensten und Impfungen liegen inkonsistente Ergebnisse vor. Die Ergebnisse von zwei neueren Studien aus Deutschland weisen jedoch auf eine höhere, als nicht notwendig eingeschätzte23 Nutzung der Notaufnahmeabteilungen in Krankenhäusern durch Personen mit Migrationshintergrund hin(Schwachenwalde et al 2020, Scherer et al 2017. In erstgenannter Studie kommen die Forschenden zu dem Schluss, dass diese inadäquate Nutzung möglicherweise auf fehlendes Wissen über Alternativen zur Notversorgung zurückzuführen ist.…”
unclassified
“…However, it also showed that the prevalence of breast screening is higher among immigrant women in Northern Italy than among Italian women in Southern Italy [ 64 ]. In general, migrant women are more likely to utilize emergency health services than non-migrants [ 65 ], which is likely related to low rates of acculturation [ 66 ]. Lack of awareness and misrepresentation may also affect the lesbian, gay, bisexual and transgender community and there is a need for improved appropriate social support for sexual and gender minority BC survivors [ 67 ].…”
Section: Resultsmentioning
confidence: 99%